Aspectos psicossociais de mães de crianças com dermatite atópica - Facchin, Tatiana Helena José (2012)
Psychodermatology is the psychology cluster which specializes in skin related issues, especially for skin chronic diseases. Among these illness, stands out Atopic Dermatitis (AD), dermatosis frequently found in children, especially when there s a relative with, in addition of this diagnosis, asthma and/or rhinitis. This disease is caused by multifactorial factors, once there are immunological, genetic, infectious, environmental, food and psychosomatic factors involved. The presence of AD in a family member leads to a series of changes and adaptations in that institution, because it is a chronic dermatosis with intense pruritus, which causes disturbances in sleep and daily activities, besides having the possibility of financial, social and emotional impact. Thus, it is understood this illness as psychosomatic, because there is an knowledge of inter-relationship between mind and body, in which the disease, regardless of its etiology, breaks the human s existing homeostasis among physical, psychological, social and spiritual. Joyce McDougall is one of the most relevant authors of psychosomatics. Her work focuses on mother-infant relationship, and this has a decisive role in psyche forming. According to her, the disease emergence in a child can be resulting of the anger that a kid feels about the mother figure, when this does not suit his/hers needs, directed by him/herself, in other words, the child somaticizes to not develop a psychosis. Other authors indicate that the mother s emotional condition is essential for the presence or absence of health, especially in the earlier stage of the child. Yet, according to Spitz, Winnicott, Anzieu and Montagu, skin and touch are fundamental to the psychic apparatus development. So, evidences the relationship between the skin disease and the early mother-child relationships. This dissertation is organized in the following way: first is presented a systematic review about the term Psychodermatology in Brazil, in databases: Lilacs, Medline, EBECS, Scielo and Pepsic. 271 articles were found, of which 28 met the inclusion criteria (publications from 2001 to 2011, written in Portuguese, with available abstracts). The results demonstrate that most publications (n=10) refers to case studies or literature reviews (n=8). Only one intervention study was found. These findings denote the need for more research in this area, especially for interventions targeted in the area of skin. The second section presents an empirical study, focused on the children with Atopic Dermatitis mothers, in order to better understand the psychosocial aspects of these, as well as the relation between them and their children. For this purpose, it is a qualitative study, conducted through interviews with mothers of five children between 6 and 9 years old. Interviews were analyzed according to Sistemic Though proposed by Morin. There were found seven thematic axis: the mother s feelings about the diagnosis; because of pregnancy; changes in routine and environment; feelings towards AD; social support; relationship with her husband; and relationship with the child, all of them permeated by the organizer: Atopic Dermatitis. It is observed that the participants have a great emotional distress related to AD. Furthermore, they are the main carers of the children, which generates feelings of loneliness. The findings of this study show a public health problem: AD has a high incidence and psychosocial impact, however, doctors, sometimes, do not feel capable of diagnosing skin diseases, and there is a lack of specialized services for this population. It is clear the need for integrated medical and psychological treatment; for this, it is necessary technical training for appropriate care and humanized attention.